Panel on Open Library, Scholarship and Learning at Athabasca University - Ives, Cindy; Elliott, Colin; Anderson, Terry (2010)
Tony Tin, founder of Athabasca University's digital content repository, AUSpace, discusses the organization of AUSpace, its benefits for open access support, researchers and organizations, and research findings of AUSpace use. Dr Terry Anderson, Canada Research in Distance Education at Athabasca University, overviews open scholarship and his work as author and editor of open books and the International Review of research on Open and Distance Learning (IRRODL). Dr Cindy Ives, Director of the Centre for Learning Design and Development (CLDD) at Athabasca University, discusses recent projects in the CLDD that have focused on open access including initiatives to produce and share open educational resources, to use open resources in course materials, and to find and aggregate open materials for adaptation and inclusion in program development. Colin Elliott, Digitization co-ordinator with AU Library Service, discusses the Bibliography of the Athabasca River Basin (BARB) which is being developed as an open access research tool to aid in the study and dissemination of research done within the basin. This presentation will focus on the ways in which open access will benefit the BARB project.